Dynamic Stability Improvement of a Multi-Machine Power System Connected with a DFIG-Based Wind Farm Using a Generalized Unified Power-Flow Controller (GUPFC) - Nguyen, Thi Mi Sa; Ngo, Van-Thuyen (Old Journal, 2017)
This paper proposes the dynamic stability improvement of a multi-machine power system which consists of conventional synchronous generators (SGs)-based power plant integrated with a doubly-fed induction generator (DFIG)-based wind farm by using a generalized unified power-flow controller (GUPFC). In addition to the power flow control function of the GUPFC, a proportional-integral-derivative (PID) type oscillation damping controller (ODC) is designed for the GUPFC to offer adequate damping for the studied system. The proposed ODC for the GUPFC is designed using the pole assignment method based on modal control theory. The steady-state analysis and time-domain simulation results show that the designed ODC for the GUPFC can significantly increase the damping and, hence, effectively improve the dynamic stability of the studied system under various disturbance conditions.